Highly Efficient Dual-Beam Frequency Scanning Based on SSPPs With Parasitic Patch Array - Pan, Bai Cao; Guo, Ben Jian; Yu, Ping; Cai, Ben Geng; Dai, Xi Wang; Luo, Guo Qing (Frontiers in Physics, 2022)
A leaky-wave antenna (LWA) realizes radiation of travelling wave along guiding structures. Periodic modulation is an effective approach to turn non-radiating modes into radiating modes. A high-efficient LWA based on spoof surface plasmon polaritons (SSPPs) loaded with parasitic patch array is proposed. Sinusoidal modulation is used for the radiation of SSPPs, while parasitic array mitigates the open stopband (OSB) effect. A prototype is fabricated and measured. The measured and simulated results agree well with each other. Such design shows wide angle coverage of 83° from backward to forward and stable gain distribution of about 12 dB within the whole operating band.